Do the benefits outweigh the risks? Potential dangers associated with long-term therapy of proton pump inhibitors - Wolanin, Izabela; Zielonka, Bartłomiej; Dengler, Barbara; Madej, Karolina; Wolanin, Marta; Stachyra, Bartłomiej; Stawikowski, Cezary; Osińska, Aleksandra; Kowalczyk, Ilona; Krasa, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction:Proton pump inhibitors (PPIs) are one of the most popular and also one of the most commonly prescribed medications worldwide. In many conditions associated with excessive secretion of hydrochloric acid in the stomach, they are the first-line treatment. When they are used in a balanced manner in strict indications, they have a high level of efficacy and a favorable safety profile. The low rate of side effects refers mainly to their short-term use. With the over-the-counter availability of PPIs, increasing dangerous trend of their abuse has provided new evidence suggesting the presence of numerous, more serious side effects of long-term PPI therapy. Purpose:The purpose of this review is to summarize current reports regarding the potential risks and causal relationship of adverse effects occurring as a consequence of long-term use of proton pump inhibitors. Material and methods:This literature review based on the available scientific literature, published between 2015 and 2023 in the Pubmed database, searched using the terms, listed under "keywords”. Conclusion:PPIs are relatively safe drugs. However, they are not completely free of side effects. There are a lot of reports suggesting a potential connection between their long-term use and the development of complications, such as: various infections, decreased absorption of nutrients, kidney disease, liver disease, pancreatic disease, musculoskeletal disease, nervous system disease, cardiovascular disease, dementia, hypergastrinemia and even cancer. However, some of them are fraught with errors, and another often provide contradictory results. More precisely designed studies are needed to draw clear conclusions, especially in view of the ever-increasing abuse of PPIs worldwide. It is worth noting that patients with strictly defined indications for long-term PPI therapy, may benefit significantly outweighing the potential dangers.